Association of Non Epileptic Seizures and Epilepsy:2 Cases Reports of Masturbation Seizures - Mariam DOUMBIA-OUATTARA; Léonard KOUASSI; Ismaïla DIAKITE; Tchwa Muriel AMON-TANOH; Constance YAPO-EHOUNOUD (Journal of Neurological Research And Therapy, 2017)
Introduction: Non epileptic seizures (NES) are little reported in our country. Case report: We report 2 observations of 4 years old girls, with normal psychomotor development, and frequent paroxystic seizures, characterized by stereotyped movements of the members, occurring during sleep onset or deep sleep. Electroencephalogram Sleep records showed brief discharges of spikes and spikes-waves. Magnetic Resonance Imaging was normal. Suspicion of NES associated with epilepsy was based on the following arguments: mild regression of the seizures frequency after using antiepileptic drug video records of the seizures strongly suggestive of masturbation seizures, masturbation seizures are triggered by the girls and stopped on order, best regression of the seizures frequency after adjunction of trihexiphenidyl. Moreover, the authors make a review of literature on the NES. Conclusion: The early diagnosis of the NES allows to avoid the inadequate treatments and an improvement of the prognosis.
Keywords: Non epileptic seizures